How do Malawian women rate the quality of maternal and newborn care? Experiences and perceptions of women in the central and southern regions - Kambala, Christabel (BMC Pregnancy Childbirth, 2015)
BACKGROUND: While perceived quality of care is now widely recognized to influence health service utilization, limited research has been conducted to explore and measure perceived quality of care using quantitative tools. Our objective was to measure women’s perceived quality of maternal and newborn care using a composite scale and to identify individual and service delivery factors associated with such perceptions in Malawi. METHODS: We conducted a cross-sectional survey in selected health facilities from March to May 2013. Exit interviews were conducted with 821 women convenience sampled at antenatal, delivery, and postnatal clinics using structured questionnaires. Experiences and the corresponding perceived quality of care were measured using a composite perception scale based on 27 items, clustered around three dimensions of care: interpersonal relations, conditions of the consultation and delivery rooms, and nursing care services. Statements reflecting the 27 items were read aloud and the women were asked to rate the quality of care received on a visual scale of 1 to 10 (10 being the highest score). For each dimension, an aggregate score was calculated using the un-weighted item means, representing three outcome variables. Descriptive statistics were used to display distribution of explanatory variables and one-way analysis of variance was used to analyse bivariate associations between the explanatory and the outcome variables. RESULTS: A high perceived quality of care rating was observed on interpersonal relations, conditions of the examination rooms and nursing care services with an overall mean score of 9/10. Self-introduction by the health worker, explanation of examination procedures, consent seeking, encouragement to ask questions, confidentiality protection and being offered to have a guardian during delivery were associated with a high quality rating of interpersonal relations for antenatal and delivery care services. Being literate, never experienced a still birth and, first ANC visit were associated with a high quality rating of room conditions for antenatal care service. CONCLUSIONS: The study highlights some of the multiple factors associated with perceived quality of care. We conclude that proper interventions or practices and policies should consider these factors when making quality improvements. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12884-015-0560-x) contains supplementary material, which is available to authorized users.